The Use of ChatGPT Application to See the Relationship between English Knowledge and Access to Obtain Information Related to Agribusiness and Physiotherapy - Sengkey, Rafael; Rompis, Lianly; Mamuaja, Filly; Paendong, Stella (European Journal of Applied Sciences, 2024)
English plays an essential role in the current era of globalization, especially in the fields of Agribusiness and Physiotherapy which require the latest information for the development of science and skills. English is also needed by both fields related to communication, research collaboration, marketing, and international cooperation. This study examined the relationship between English knowledge and access to information related to Agribusiness and Physiotherapy, whether having good English skills will be able to increase their knowledge more widely than those who have lower English skills. The supporting application that was used in this study was ChatGPT application and the research method used was Central Tendency Measurement and Simple Linear Regression Analysis.